2001
DOI: 10.1002/j.1556-6978.2001.tb01277.x
|View full text |Cite
|
Sign up to set email alerts
|

Novice Supervisees' Self‐Evaluations and Their Perceptions of Supervisor Style

Abstract: Multiple regression analyses of data obtained for 36 counseling supervision dyads indicated that attractiveness, an aspect of supervisory style, was negatively associated with supervisees' self-evaluations and positively associated with the difference between trainees' and supervisors' evaluations of counseling competence at the end of the 1st practicum experience. Supervisors' interpersonal sensitivity and task orientation were not found to contribute significantly to either of the criterion variables.Supervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 15 publications
0
20
1
Order By: Relevance
“…Like Ladany, Marotta et al (2001), Fernando and Hulse-Killacky concluded that supervisors need to be proficient in all three styles and be flexible in their use. Steward, Breland, and Neil (2001) explored the influence of novice supervisees' preferences for supervisor style on their self-evaluations. The supervisees (n = 36, mostly White females) completed a non-standardized counselor competence rating scale at the end of the semester.…”
Section: Supervision In Counseling: Interdisciplinary Issues and Resementioning
confidence: 99%
“…Like Ladany, Marotta et al (2001), Fernando and Hulse-Killacky concluded that supervisors need to be proficient in all three styles and be flexible in their use. Steward, Breland, and Neil (2001) explored the influence of novice supervisees' preferences for supervisor style on their self-evaluations. The supervisees (n = 36, mostly White females) completed a non-standardized counselor competence rating scale at the end of the semester.…”
Section: Supervision In Counseling: Interdisciplinary Issues and Resementioning
confidence: 99%
“…Extensive literature exists on the perceptions of supervisees regarding the supervision process and relationship (Ladany, Ellis, & Friedlander, 1999;Ladany, Walker, & Melincoff, 2001;Pearson, 2000;Schlosser & Gelso, 2001;Steward, Breland, & Neil, 2001;Sumerel & Borders, 1996). Very little is known, however, regarding the effects of different models of supervision.…”
Section: Abstract Supervision Supervision Models Individual/triadimentioning
confidence: 99%
“…The term style was used in the present study and is in agreement with the conceptualization of Ladany,Walker,and Melincoff (200 1), whose definition of supervision styles includes not only the "distinctive manner of responding to supervisees" but also the "different approaches the supervisors use" (p. 263). A line of research has identified support and direction as supervisor behavior that underlies all of the various styles of supervision (Bernard, 1997;Blocher, 1983;Holloway & Hosford, 1983;Steward, Breland, & Neil, 2001;Stoltenberg et al, 1998;Worthington & Roehlke, 1979). Support refers to those behaviors that show empathy and build rapport with the supervisee.…”
mentioning
confidence: 99%